2014
DOI: 10.1051/0004-6361/201322493
|View full text |Cite
|
Sign up to set email alerts
|

CoRoT 223992193: A new, low-mass, pre-main sequence eclipsing binary with evidence of a circumbinary disk

Abstract: We present the discovery of CoRoT 223992193, a double-lined, detached eclipsing binary, comprising two pre-main sequence M dwarfs, discovered by the CoRoT space mission during a 23-day observation of the 3 Myr old NGC 2264 star-forming region. Using multi-epoch optical and near-IR follow-up spectroscopy with FLAMES on the Very Large Telescope and ISIS on the William Herschel Telescope we obtain a full orbital solution and derive the fundamental parameters of both stars by modelling the light curve and radial v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 100 publications
3
63
0
Order By: Relevance
“…The Sung et al (1997) distance is in good agreement with a recent VLBI distance for a maser source in the cluster (d = 738 +57 −50 pc; Kamezaki et al 2014) and with a recent analysis of data for a newly identified NGC 2264 pre-main sequence EB (d = 756 ± 96 pc; Gillen et al 2014). …”
Section: Physical Properties Of the Short-duration Flux Dip Classsupporting
confidence: 89%
See 1 more Smart Citation
“…The Sung et al (1997) distance is in good agreement with a recent VLBI distance for a maser source in the cluster (d = 738 +57 −50 pc; Kamezaki et al 2014) and with a recent analysis of data for a newly identified NGC 2264 pre-main sequence EB (d = 756 ± 96 pc; Gillen et al 2014). …”
Section: Physical Properties Of the Short-duration Flux Dip Classsupporting
confidence: 89%
“…Figure 2 shows two eclipsing binary (EB) light curves from the 2008 NGC 2264 campaign. Figure 2(a) is the light curve for Mon-256, a dM-dM binary member of NGC 2264 (Gillen et al 2014) that is a borderline CTTS (broad and structured Hα profile; modest IR excess); this is the only EB in NGC 2264 with an IR excess presumably due to circumstellar Cody et al (2014) and the Appendix for the sources of the spectral type and Hα equivalent width (EW) data. Here we use the convention that negative values are in emission, which is opposite to the convention in Cody et al (2014).…”
Section: Aperiodic Extinctors (Examples Illustrated Inmentioning
confidence: 99%
“…The GP model utilizes the george package 7 (Ambikasaran et al 2014) and is used to model the out-of-eclipse (OOE) photometric data. A detailed description of GP regression is beyond the scope of this paper but the interested reader is referred to Roberts et al (2012) for a gentle introduction, Rasmussen & Williams (2006) for a more detailed entry, Aigrain et al (2012) for application to stellar light curves, and Gillen et al (2014) for application to EB light curves and cross-correlation functions.…”
Section: Gp-ebopmentioning
confidence: 99%
“…Also displaying fading behavior but in a strictly periodic manner are the eclipsing binaries of NGC 2264. The most intriguing of these exhibits aperiodic out-of-eclipse variability indicative of a circumbinary disk ( [10]). While the dippers and eclipsing binaries display fading, the opposite behavior appears in stars that we refer to as "bursters"-objects with frequent episodes of rapidly increasing flux.…”
Section: Light Curve Classification Schemementioning
confidence: 99%